PENDIDlKAN ISLAM MENUJU MASYARAKAT MADANI - Ajat Sudrajat Ajat Sudrajat (LPMPP Universitas Negeri Yogyakarta, 1999)
The concept of a civil society which has become a newdiscourse in the life of a nation has received positive responsenot only om the intellectual circles but also from high-rankinggovernment officials in Indonesia, including President BJHabibi and Minister of Defence and Security, General WirantoThey have even rethorically expressed the idea of a futureIndonesia in a civil society format. Therefore, all the nation'spolitical, social, economic, military, and educational potentialis being directed towards such a society.A civil society has at least three characteristics, i e.,( 1 ) the eis a sufficiently high degree of autonomy of ndiv duaalsn d groups in the society in their interactionwith the state, (2) there is free public space for the expresslonof individual and group political activity in the society,and (3) there is an individual and group capacity of refiisit gstate or gover iiitnntet ventionin the society.Tqlamir rtlt c-atinna .: part of thr national educationalpotential, has a share in the responsibility of building a civilsociety. For that, there are characteristics of Islamic educatlonwhich, in terms of institutional matter, educational process,and educational material, need to undergo reformation.Only 11t.Ins larttic educalior re sult in a self-supporting institutlonand produce human resources prepared to confrontlife's challenges and filled with enough tolerant attitude inthe face of differences.